Enhanced discontinuity mapping of rock slopes exhibiting distinct structural frameworks using digital photogrammetry and UAV imagery - Hartwig, Marcos Eduardo; Santos, Garion Guidotti de Souza dos [UNESP] (Springer Nature, 2024)
The Structure-from-Motion-Multi-View Stereo (SfM-MVS) techniques with high-resolution photographs acquired with unmanned aerial vehicles (UAVs), were applied to investigate rock slopes with distinct structural styles. Photos were captured with varying flight plan settings, including manual and automatic overflights with fixed and unfixed gimbal pitch angle. The 3D point clouds were generated with the Agisoft Metashape software and segmented in the CloudCompare software (plugin FACETS) to identify the discontinuity systems. A comparison between digital and compass-based measurements was conducted to validate the accuracy of the 3D digital outcrop models. The study area comprises two vertical cut slopes situated in southeastern Brazil: one in a basalt quarry in Iracemápolis municipality, São Paulo State, and another at km 6 of the ES-482 highway, Espírito Santo State, excavated in poorly fractured banded gneiss. The results revealed that the automatic overflight produced a more accurate 3D digital outcrop model compared to the manual overflight, owing to the regularity of the photo grid. Additionally, the automatic overflight with an unfixed gimbal pitch angle configuration provided the most accurate 3D digital outcrop model. SfM-MVS techniques with drone photos provide better coverage of the rock slope compared to the traditional scanline method. However, the latter remains crucial in structural surveys because the data facilitate the segmentation and interpretation of the digital outcrop models, allowing for the differentiation of discontinuity types and thereby enhancing structural mapping accuracy.